Features of the cytokine profile and the effectiveness of radical treatment of focal infection in patients with psoriasis - Aleksandr V. Patrushev (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Background. Focal infection (FI) are important trigger factors for the development of psoriasis, which means they can aggravate the course of dermatosis, including due to an increase in certain pro-inflammatory cytokines in the blood.